Managing the human side of information technology challenges and solutions - Szewczak, Edward.; Snodgrass, Coral. (IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2002)
"This book addresses how to effectively manage the ways in which information technology impacts both human and organizational behavior"--Provided by publisher.